(untitled) (Communications in Mathematical Research, 2019)
In this paper, we focus on how to use strain energy minimization to obtain the optimal value of the free parameter of the planar Cardinal spline curves. The unique solution can be easily obtained by minimizing an appropriate approximation of the strain energy. An example is presented to illustrate the effectiveness of our method.